Pentaethylenehexamine-C60 for Temperature Consistent Carbon Capture - Enrico Andreoli (C—Journal of Carbon Research, 2015)
Fullerene C60 is directly added to and reacted with plain pentaethylenehexamine (PEHA) to give PEHA-functionalized C60 powders. The CO2 capture performance of PEHA-C60 appears to be consistent across a range of temperatures wider than that of polyethyleneimine (PEI)-modified C60, whose high CO2 capture performance drops rapidly with decreasing temperature. At about 30 °C, the CO2 capture capacity of PEHA-C60 is six times higher, 65 mg CO2/g sorbent, than that of PEI-C60, 10 mg/g. In contrast to PEI, PEHA reacts with C60 to form products of greater porosity and smaller particles size that allow for a faster contact between CO2 and amine functions. This in turns translates into a lower energy requirement for CO2 sorption and desorption.